CRITICAL THINKING, CLINICAL REASONING SKILLS AND COGNITIVE ABILITIES OF DENTAL STUDENTS - Bernadetta Esti Chrismawaty; Ova Emilia; Gandes Retno Rahayu; Ika Dewi Ana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Critical thinking (CT) and clinical reasoning (CR), along with adequate clinical knowledge, are crucial components of thinking in clinical practice. This study aimed to assess, compare and analyze the relationship between CT skills, CR skills, and cognitive abilities in undergraduate (UDS) and clinical dental students (CDS).Methods: This natural experimental study was conducted using the quantitative descriptive-analytic methods with a cross-sectional design. Thirty UDS and sixty-one CDS were selected purposively. Demographic and academic data were obtained through questionnaires. The Critical Thinking Tool (CriTT) was used to measure CT skills, and CR skills were measured by the Diagnostic Thinking Inventory (DTI). Knowledge acquisition was measured through the Cognitive Ability Test (CAT), which is a set of multiple-choice questions specifically developed and validated for this study. The statistical differences between them were analyzed by one-way ANOVA, and their relationship was tested by correlation matrix analyses.Results: There were no differences in CriTT measurements between groups. The overall DTI score and subscale 2 (Structure of memory) showed significant differences between groups, as did the overall CAT score and all clinical science subscales. Correlation matrix analyses revealed CR skills were related to CT skills, while the cognitive abilities or knowledge acquisition were related to CR skills.Conclusion: Results showed the CR skills and cognitive abilities of clinical dental students are superior to undergraduate dental students. Generally, the results indicated the more skilled students are in critical thinking, the better are their clinical reasoning skills. Better cognitive abilities tended to improve clinical reasoning skills.